Ball Burnishing For The Formation Of A Regular Helical Relief On LoadBearing Surfaces Of Transport Machine Components (Eurasian Research Bulletin, 2026)
The process of external ball burnishing for the formation of a regular helical relief on the load-bearing surfaces of transport machine components is considered. Based on Hertzian contact theory, the conditions for plastic deformation of the surface layer are established, and estimates of strengthening are provided. The formation of compressive residual stresses in steel 20 is confirmed, ensuring an increase in the fatigue strength of the components.